Factors Affecting Knowledge Management: A Study in Al-Madinah International University, Malaysia - Bhutto, Dr. Sana Arz; Khoso, Dr. Ubedullah; Mehmood, Dr. Kashif (The journal of contemporary issues in business and government, 2022)
The aim of this study is to investigate the factors which can affect the knowledge management in Al-Madinah International University, Malaysia. This study employs a quantitative methodology for whichquestionnaires were distributed to on-campus staff at the university and a sample of 138 responses was collected for multiple regression analysis. Statistical Packages (SPSS) software was used to analyze the structure model. The results show that the motivation factors such as social interaction, trust, management support, learning orientation and motivation can provide explanation of knowledge sharing. This study found a positive correlation between sharing knowledge and the social interaction. Therefore, this study suggests that when knowledge is built and is shared then it creates a positive impact on an organizations employees. This study will contribute to the literature in the field of knowledge sharing. Comparatively, the studies focusing on knowledge sharing among Malaysian universities are limited.